Calculation of Penalties in Algorithm of Mixed Integer Programming Solving with Revised Dual Simplex Method for Bounded Variables (Journal of Computational Mathematics, 1999)
The branch-and-bound method with the revised dual simplex for bounded variables is very effective in solving relatively large-size integer linear programming problems. This paper, based on the general forms of the penalties by Beale and Small and the stronger penalties by Tomlin, describes the modifications of these penalties used for the method of bounded variables. The same examples from Petersen are taken and the satisfactory results are shown in comparison with those obtained by Tomlin.
Keywords: Penalties; Stronger penalties; The revised dual simplex method for bounded variables.